Dietary Lipid Intake only Partially Influences Variance in Serum Phospholipid Fatty Acid Composition in Adolescents: Impact of Other Dietary Factors. Issue 9 (14th August 2014) - Vyncke, Krishna; Huybrechts, Inge; Van Winckel, Myriam; Cuenca Garcia, Magdalena; Labayen, Idoia; Gottrand, Frederic; Widhalm, Kurt; Leclercq, Catherine; Libuda, Lars; Manios, Yannis; Sjostrom, Michael; Molnar, Denes; et al.
Abstract: The present study aimed to assess the correlation between food and fatty acid (FA) intake and the serum phospholipid (PL) FA status in European adolescents and explored the percentage of variation in serum PL FA that could be attributed to dietary habits. Participants included 528 adolescents recruited in the HELENA Study. Dietary intake was assessed by two, self‐administered, non‐consecutive 24‐h recalls. PL FA concentrations were measured in fasting venous serum samples. Reduced rank regressions were applied to examine the combined effect of food intakes. Results indicated that the variance in serum PL FA in adolescents, that could be explained by diet varied from 7.0 % for MUFA to 14.2 % for n‐3FA. The variance in the long‐chain n‐3FA was mainly explained by fish intake but also by coffee and tea consumption. In conclusion this study indicated that dietary intake influences the serum PL FA status to a limited amount but that also other factors interfere. However, dietary intake is important as it is among those factors that could be modified. Furthermore, the results suggest that the overall dietary habits should be considered instead of only the consumption of single foods or nutrients, as the medium of the food or concomitant intake of foods and nutrients might interact and as such influence absorption or metabolism.